2020
DOI: 10.48550/arxiv.2012.06792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the dynamical behaviour of the generalized Ricci flow

Alberto Raffero,
Luigi Vezzoni

Abstract: Motivated by Müller-Haslhofer results on the dynamical stability and instability of Ricci-flat metrics under the Ricci flow, we obtain dynamical stability and instability results for pairs of Ricci-flat metrics and vanishing 3-forms under the generalized Ricci flow.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A Perelman-type F-functional for this was found in [19], and an expander entropy functional was found in [26]. Some recent results in the homogeneous setting have appeared [20], as well as a stability result near Ricci-flat metrics [23]. In [9] it was shown that the equation reduces to Ricci-Yang-Mills flow in the case of a U (1) principal bundle over a Riemann surface.…”
Section: Symmetry Reductionsmentioning
confidence: 96%
“…A Perelman-type F-functional for this was found in [19], and an expander entropy functional was found in [26]. Some recent results in the homogeneous setting have appeared [20], as well as a stability result near Ricci-flat metrics [23]. In [9] it was shown that the equation reduces to Ricci-Yang-Mills flow in the case of a U (1) principal bundle over a Riemann surface.…”
Section: Symmetry Reductionsmentioning
confidence: 96%